Disease complex associated with begomoviruses infecting squash and cucumber in Saudi Arabia: Begomovirus complex infecting cucurbits in Saudi Arabia - Amer, Mahmoud Ahmed; Khalid, Zaheer; Hussain, Khadim; Al-Shahwan, Ibrahim; Ali Al-Saleh , Mohammed (Cellular and Molecular Biology, 2024)
During the field visits in growing season of 2022 in Dammam Region of Saudi Arabia, begomovirus-like symptoms including leaf curling, leaf cupping, leaf distortion, vein thickening and reduced leaf size were observed in squash and cucumber fields. Twenty-five samples were collected from each crop and PCR amplification was done using general diagnostic begomovirus primers (AC-1048/AV-494 and Begomo I/Begomo II). The obtained results showed desired sized amplified DNA fragments (550 bp and 1.1 kb) according to the primer sites. Sequencing results were analyzed using BLAST and revealed the presence of three different bipartite begomoviruses which include Squash leaf curl virus (SqLCV) isolated from squash and cucmber, Watermelon chlorotic stunt virus (WmCSV) and Tomato leaf curl Palampur virus (ToLCPalV) isolated from squash. The highest nucleotide identity found was 99.4% with Egyptian SqLCV isolated from squash and the lowest similarity was 93.3% found with a USA isolate isolated from wheel cactus. Sequencing results of two isolates of WmCSV showed 100% sequence identity with each other, eight isolates from Palestine isolated from watermelon, two isolates from Mexico isolated from prickly pear cactus and Watermelon, one isolate from each Lebanon and Jordan isolated from melon and wild mustard respectively. The lowest identity (87%) was found with a Saudi Arabian isolate isolated from papaya. For ToLCPalV isolate showed the highest identity (100 %) with an already reported isolate of same virus from melon in Saudi Arabia and two isolates isolated from cucumber and cantaloupe in Iran. However, the lowest identity (95.3%) was found with an Indian isolate isolated from eggplant. This is the first investigation of complex viral disease caused by SqLCV, WmCSV and ToLCPalV on the basis of molecular characterization from squash and a SqLCV isolate from Cucumber in Saudi Arabia.